The Effect of Hardening Process on SKD 61 Material using Single Quenching and Double Quenching Techniques on Its Mechanical Properties - Wiradinata, Trisna Ardi; Nopryandi; Daryus, Asy'ari; Bagas, Stefanus; Sugiyanto, Didik (Universitas Negeri Jakarta, 2025)
This study focuses on investigating the effects of Single quenching and double quenching techniques on the mechanical properties of SKD 61 material, particularly in the context of bending strength and hardness measured using the Brinell hardness test. The research method involved heating SKD 61 specimens to 1000°C for 15 minutes, followed by cooling using oil and air as quenching media. The results showed that the single quenching technique with oil medium increased the bending strength from 406.89 to 435.84 N/mm² and the hardness from 255 to 315 HB. The single quenching technique using air increased the bending strength to 410.88 N/mm² and the hardness to 290 HB. Meanwhile, the double quenching technique using a combination of oil and air produced a bending strength of 430.08 N/mm² and a hardness of 305 HB. These improvements are based on average values, and no statistical significance testing was conducted. These findings suggest that the appropriate selection of quenching media can optimize the mechanical properties of SKD 61, which is crucial for industrial applications requiring a combination of high toughness and strength.